PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT BANK SINARMAS KCP. A. YANI BANJARMASIN - Mohdari Mohdari; Rizki Amalia Afriana; Masrifani Masrifani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstrack, The research aim to analyze the influince quality of service to customer satisfaction at PT Bank Sinarmas KCP A. Yani Banjarmasin. Service quality in this research using tangible variables, reliability, responsiveness, assurance, and empathy. The research method used is quantitative analysis, which connects service variables with customer satisfaction and types of respondents including validity and reliability tests, classic assumption tests, multiple linear regression analysis, t test and F test and the coefficient of determination. The results found in the tangible hypothesis test, reliability, responsiveness, assurance and empathy have a simultaneous effect on customer satisfaction of PT Bank Sinarmas KCP A. Yani Banjarmasin. The results of the reliability and responsiveness hypothesis test have a partial effect on customer satisfaction of PT Bank Sinarmas KCP A. Yani Banjarmasin. Hypothesis test results reliability variable dominant effect on customer satisfaction PT Bank Sinarmas KCP A. Yani Banjarmasin.